Alfabetização de estudantes surdos: uma reflexão necessária - NASCIMENTO, Fabrício Leal do (2024)
The aim of this study is to discuss on the literacy process of deaf students. The text brings some notes on the pedagogical doing in the literacy of deaf students. A bibliographical research based on Gil (2002) was carried out. It was used as a basis for discussion the authors; Monteiro (2016); Ziesmam (2007); Sterwart (1993), among others. The results indicate that the literacy of deaf people should be carried out first in sign language (L1), because this process will make all the difference in the education and social development of this collective; however, the Portuguese language (L2) must be taught together; and for the effectiveness of this teaching process for deaf students, one can also see the importance of the interpreter of pounds in the context of the classroom that contributes positively to the sociability of the student with deafness within the school space and, consequently, in coexistence in society.